Comparison of Selection Traits for Effective Popcorn (Zea mays L. var. Everta) Breeding Under Water Limiting Conditions - Kamphorst, Samuel Henrique; Amaral Júnior, Antônio Teixeira do; de Lima, Valter Jário; Santos, Pedro Henrique Araújo Diniz; Rodrigues, Weverton Pereira; Vivas, Janieli Maganha Silva; Gonçalves, Gabriel Moreno Bernardo; Schmitt, Katia Fabiane Medeiros; Leite, Jhean Torres; Vivas, Marcelo; Mora-Poblete, Freddy; Vergara-Díaz, Omar; et al. (Frontiers in Plant Science, 2020)
Climate change is expected to intensify water restriction to crops, impacting the yield potential in popcorn. This work aimed to evaluate the performance of 10 field cropped popcorn inbred lines cultivated, in two seasons, under well-watered (WW) and water stressed (WS) (ψsoil ≥ - 1.5 MPa) conditions applied by withholding irrigation in the phenological phase of male pre-anthesis. Additionally, two contrasting inbred lines, P7 (superior line) and L75 (less performer) for grain yield (GY) and expanded popcorn volume (EPV), selected from previous studies, were tested in detail under greenhouse conditions. Under field no genotype x water condition x crop season (G×WC×CS) interaction was observed, whereas GY (-51%), EPV (-55%) and leaf greenness (SPAD index) in measurements after 17 days after anthesis (DAA) (> -10 %) were highly affected by water limitation. In general, root traits (angles, number and density) presented G×WC×CS interaction, which do not support their use for selection. Related to leaf senescence, for both WS and WW conditions, the superiors inbred lines maintained a stay-green condition (higher SPAD index) until physiological maturity, but SPAD index maximum values were observed later in WW (48.7, by 14 DAA) than in WS (43.9 by 7 DAA). Under both water conditions, negative associations were observed between SPAD index values 15 and 8 days before the anthesis DBA), and GY and EPV (r ≥ -0.69), as well as between SPAD index 7, 17 and 22 DAA, and angles of brace root (AB), number of crown roots (NC) and crown root density (CD), in WS (r ≥ -0.69), and AB and CD, in WW (r ≥ -0.70). Lower values of NC and CD may allow further root deepening in WS condition. Under WS the P7 maintained higher values of net photosynthesis, stomatal conductance and transpiration, than L75. Additionally, L75 exhibited a lower (i.e., more negative) carbon isotope composition values than P7 under WS, confirming a lower stomatal aperture in L75. In summary, besides leaf greenness, traits informing on the photosynthetic status of the leaf and stomatal conductance, showed to be good indicators of the agronomic performance of popcorn under water constraints.